Experimental investigation of natural circulation instability in a BWR-type small modular reactor. (November 2015) - Shi, Shanbin; Schlegel, Joshua P.; Brooks, Caleb S.; Lin, Yu-Chen; Eoh, Jaehyuk; Liu, Zhuo; Zhu, Qingzi; Liu, Yang; Hibiki, Takashi; Ishii, Mamoru
Abstract: The Purdue NMR (Novel Modular Reactor) represents a BWR-type small modular reactor with a significantly reduced reactor pressure vessel (RPV). Specifically, the NMR is one third the height and area of a conventional BWR RPV with an electrical output of 50 MWe. Experiments are performed in a well-scaled test facility to investigate the thermal hydraulic flow instabilities during the startup transients for the NMR. The scaling analysis for the design of natural circulation test facility uses a three-level scaling methodology. Scaling criteria are derived from non-dimensional field and constitutive equations. Important thermal hydraulic parameters, e.g. system pressure, inlet coolant flow velocity and local void fraction, are analyzed for slow and fast normal startup transients. Flashing instability and density wave oscillation are the main flow instabilities observed when system pressure is below 0.5 MPa. And the flashing instability and density wave oscillation show different type of oscillations in void fraction profile. Finally, the pressurized startup procedure is recommended and tested in current research to effectively eliminate the flow instabilities during the NMR startup transients. Highlights: Overview of typical flow instabilities occur during NCBWR startup. Introduction of a new well scaled natural circulation test facility. Evaluation of scaling distortions by RELAP5 analysis and characteristic tests. Identification of flow instabilities during low pressure startup transients of NMR. Testing of pressurized startup procedures to eliminate flow instability.